Perspektif Al-Qur’an tentang Pembebasan Manusia melalui Pendidikan Akhlak - Ainusyamsi, Fadlil Yani; Husni, Husni (Jurnal Penelitian Pendidikan Islam, 2021)
This study aims to elaborate the concepts of the Qur'an about moral education. In addition, this study also aims to understand the concept of human liberation in the Qur'anic perspective. This study uses the literature review method by tracing a number of verses of the Qur'an that are relevant to the theme of the study. In addition to examining relevant verses of the Qur'an, this study is also equipped with a reflection method, which is a method that seeks to reflect the author's knowledge and experience in the current context, so that the author's knowledge and experience are used as a mirror in understanding the realities and problems of Muslims. The results of the study show that efforts to improve the character and behavior of Muslims are to free mankind from ignorance, poverty, and neglect of Islamic moral values.